Interlineation of the functions of the three variables on a system of disjoint lines preserving the differentiability class - Sergienko, I. V.; Lytvyn, O. N.; Lytvyn, O. O.; Tkachenko, A. V.; Gritcai, O. L. (Reports of the National Academy of Sciences of Ukraine, 2015)
A method of construction of Hermitian-type operators of interlineation of the functions of three variables with help of traces and traces of derivatives on the given lines is proposed. The method can recover these functions at points between the given system of closed disjoint lines in a cylindrical coordinate system, automatically preserving the differentiability class of an approximated function.